Most and least important attributes for domestic travel: A best-worst scaling approach - Lee, Soyeun Olivia; Kim, JooHyang; Han, Heesup (Frontiers in Psychology, 2022)
This study identifies the most important and least important selection attributes in Korean domestic travel during the COVID-19 pandemic. A total of 632 responses were used as the final analysis by conducting a survey of Koreans who have experienced travel in Korea since the outbreak of COVID-19. In order to explain tourists' domestic travel selection preferences, best-worst scaling (BWS) was used. As a result of the study, it was found that the destination environment is most important and is considered relatively important in the order of accommodation, major activities, expenditure, and crowdedness. On the other hand, length of stay, transport mode, travel time, and media exposure showed relatively low importance. In a situation where overseas travel is unstable due to the risk of infectious diseases, it is urgent to identify changes in domestic travel trends/factors that are important to tourists and respond to their needs and expectations. This study is academically expanded in that it not only bridges the research gap that previous studies have missed but also considers and ranks the importance of domestic travel factors at the same time.